PESAN HUMANISME FOTO JENAZAH PASIEN COVID-19 KARYA JOSHI IRWANDI: - - Setiawan, Syahrul Rizki Pratama (Universitas Negeri Surabaya, 2022)
The COVID-19 pandemic is a disease outbreak in the form of a virus that is engulfing all regions in the world, as if all media and journalists flocked to report the latest conditions of the pandemic after the first spike was successful and entered the second spike phase until it was widely discussed in various media with various conditions. which exists. The main factor in this research is how in a photojournalism one can know the actual meaning and message depicted in the photo and also know what is implied or connotative. Semiotic analysis is a method used to analyze and give meaning to the symbols contained in the picture. Advances and developments in media technology increasingly require people to be more mature in understanding every news and information they will see and read. In Joshi Irwandi's photo, there is an appearance of a photo that invites reactions from the public, but in the author's view there is the meaning of the message of humanism that is implied about how the human struggle is involved in the conditions of reality in a COVID-19 emergency hospital, and gets a very special moment. interesting and holds many impressions of meaning in it that can be studied humanely. This research actually wants to show how a photo is not only a work of art or as a complement to an information, but also has an implied meaning of humanity contained in it and is also useful for humans.